(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Government policy plays a crucial role in fostering thriving corporate efforts. This study explores the impact of government policy in promoting entrepreneurship and its economic outcomes. The study showed a positive link between entrepreneurship and economic growth, highlighting the crucial role of favourable government policy in catalysing entrepreneurship development. Despite entrepreneurship recognition, its growth is constrained by several factors, such as laws, regulations, and rules. The paper prioritised entrepreneurship as vital for any national economy to thrive, establishing a basis for more studies on entrepreneurial practices and policies, to aid scholars, academics, and practitioners in comprehending the link between entrepreneurship, government policy, and economic growth. Data was obtained from empirical studies, conceptual clarifications, and content analysis of secondary data. Hence, the impact of government policy on entrepreneurship and economic growth is a critical field of study, with implications for policymakers, entrepreneurs, and the global nation’s economic growth.